Dampak Program Sekolah Lapang Pengelolaan Tanaman Terpadu terhadap Efisiensi Teknis Usahatani Kedelai di Kabupaten Jember - Indah Ibanah; Andriyono Kilat Adhi; Dwi Rachmina (Jurnal Agribisnis Indonesia, 2014)
This study aimed to analyze the impact of Sekolah Lapang Pengelolaan Tanaman Terpadu (SLPTT) on technical efficiency soybean participants and non-participants farmers. SLPTT is one of the government programs in an effort to enhancement production and productivity of soybean through the process of learning the application of technology to the management of the use of farm inputs and integrated climate. The method used was the Stochastic Frontier Analysis (SFA) with a model of the Cobb-Douglas production function. Location research in Jember Regency, East Java.The results show the factors that influence significantly to the enhancement in soybean production among others, land, seeds, chemical fertilizers, and pesticides liquid. Production factors most responsive to the enhancement in soybean production is the amount of seed used. The average level of technical efficiency of soybean farming both farmers SLPTT or non SLPTT in Jember Regency have technically efficient. However, farmers SLPTT has an average value of technical efficiency is higher than their non SLPTT, respectively worth 0.83 and 0.75. The sources that affect farmers' socio-economic enhancement of technical efficiency of soybean farming significantly among others, age, planting techniques, the use of VUB, mechanical control, and the number of counseling or SLPTT 2013.